Future Experiments of Kaon Physics - Wanke Rainer (EPJ Web of Conferences)
Several new experiments to study Kaon physics have been taken into operation in the recent years or are being planned at the moment. All of them aim to measure ultra-rare FCNC Kaon decays like K → πνν¯, KL → π0l+l−, or K0 → µ+µ−, which all are extremely sensitive to possible new physics beyond the Standard Model. This report gives an overview on the status and the physics reaches of currently running and future Kaon physics experiments.